Information relations for social change: exploring the information behaviour of academics undertaking impact work - Joann Cattlin; Lisa M. Given (Information Research: An International Electronic Journal, 2024)
Introduction. This paper examines academics’ information behaviour in undertaking research for societal impact. It explores how researcher-stakeholder relationships provide sites of information exchange where academics develop skills and knowledge needed to undertake impact work.